Pengaruh fraksi volume dan orientasi sudut serat komposit polyester-serbuk kayu ulin (eusideroxylon zwageri)-kawat kasa terhadap kekuatan bending - Akhmad Syarief; Taufik Irfansyah Sofian; Akhmad Ghiffary Budianto; Andy Nugraha (Universitas Muhammadiyah Metro, 2022)
A composite is a material formed from the combination of two or more constituent materials through an inhomogeneous mixture. The ironwood waste has less economic value, which makes the authors interested in conducting research using mosquito nets and particle composite ironwood waste. Which is to find out the effect of volume fraction and angle orientation of the fiber composite polyester-ulinwood powder (Eusideroxylon zwageri)-mosquito wire on the bending strength. The bending test was carried out using the ASTM D-790 standard with the three point bending test method and the composite was manufactured using the hand lay-up method with the particle composition: polyester: 10%: 90%, 15%: 85%, 20%: 80%, and 25%: 75%. The results obtained in the comparison of the composition of less ironwood powder, a finer mesh size with an orientation angle of 45°, and mosquito wire show the highest bending strength and high deformation ability (ductile), and the addition of mosquito net as one of the composite specimen fibers of polyester resin does not increase significant bending strength but can reduce the deformability reduction effect.